An application of q-calculus to harmonic univalent functions - Saurabh Porwal,; Ankita Gupta, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of the present paper is to introduce a new subclass of harmonic univalent functions associated with q-calculus. We obtain coefficient conditions, distortion bounds, extreme points, convolution condition and convex combination for functions belonging to this class. We also discuss a class-preserving integral operator and q-Jackson type integral operator for this class of functions.